2015
DOI: 10.1089/jir.2015.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virus Infection in Deregulating the Cytokine Response to Secondary Bacterial Infection

Abstract: Proinflammatory cytokines are produced by macrophages and dendritic cells (DCs) after infection to stimulate T helper (Th) cells, linking innate and adaptive immunity. Virus infections can deregulate the proinflammatory cytokine response like tumor necrosis factor-α and interleukin (IL)-2, making the host more susceptible to secondary bacterial infections. Studies using various viruses such as lymphocytic choriomeningitis virus, influenza A virus, and human immunodeficiency virus have revealed several intrigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Moreover, earlier studies in the lung suggest that innate immune cells in the lung are indeed able to remember their inflammatory history. Studies investigating the effect of two unrelated subsequent viral infections, LCMV and influenza A virus, clearly showed that a first infection exerts the ability to alter a secondary innate immune response indicating a degree of innate immune training in these models of viral infections (Mehta et al, 2015). Beyond host defense, the consequences of topical innate immune training or inflammatory memory for the development of autoimmune and auto-inflammatory disorders remain to be investigated.…”
Section: Central Versus Tissue Innate Immune Memorymentioning
confidence: 99%
“…Moreover, earlier studies in the lung suggest that innate immune cells in the lung are indeed able to remember their inflammatory history. Studies investigating the effect of two unrelated subsequent viral infections, LCMV and influenza A virus, clearly showed that a first infection exerts the ability to alter a secondary innate immune response indicating a degree of innate immune training in these models of viral infections (Mehta et al, 2015). Beyond host defense, the consequences of topical innate immune training or inflammatory memory for the development of autoimmune and auto-inflammatory disorders remain to be investigated.…”
Section: Central Versus Tissue Innate Immune Memorymentioning
confidence: 99%
“…Lung ILC2 were shown to be able to remember their activation status if stimulated by inhaled allergens [32]. Cytomegalovirus and influenza A can trigger a stronger NK mediated secondary innate immune response on reinfection [33]. It is demonstrated that common epigenetic mechanisms determine memory cell development, both in the adaptive and innate immune system [34].…”
Section: The Cruxmentioning
confidence: 99%
“…Furthermore, the virus alters the Toll-like receptor pathways, resulting in decreased neutrophil attraction, which in turn increases the attachment of bacterial cells onto host epithelium [7]. Additionally, infection with influenza can deregulate cytokine production through inducing type I interferon, which can down-regulate cytokine production [56]. MicroRNA-based mechanisms resulting from influenza infection can also down-regulate cytokine production.…”
Section: Indirect Interactions: Bacteria Exploiting Viral Infectionsmentioning
confidence: 99%